Perlindungan Hukum Konsumen terhadap Informasi Kandungan Zat Etilen Oksida pada Mie Instan Indomie - Nadya Smaralaksmi; Bagya Agung Prabowo (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This research is about legal protection of information on the content of ethylene oxide in Indomie instant noodle. This research is normative type. This research uses a case approach method. The data collection technique uses secondary data collection techniques. The results of the study, first, consumer legal protection in this study is still weak. Consumers do not obtain correct, clear, and honest information regarding the content of ethylene oxide levels in Indomie instant noodle packaging as they should. This causes consumer rights regarding open information not to be fulfilled properly and correctly. Second, the responsibility of business actors is not appropriate for the loss of consumers who consume Indomie instant noodle products with excess ethylene oxide levels.